Intertextuality in Antology of Poetry Essay (Research on Poetry Essay Atas Nama Cinta written by Denny JA and Poetry Essay Serat Kembang Raya written by Fatin Hamama, et al) - Septiaji, Aji (KnE Social Sciences, 2019)
Literature as one of the works that involve the text as a medium in delivering form and meanings. It has a role that affects other works or readers’ point of view. In the process of creating a work, an author is inseparable from his involvement with other texts which have existed before that surround them. It shows the inﬂuence of other texts that included into the result of literary text. Thus, there is no original text belongstoanauthor.Themethodusedinthisstudyisdescriptivequalitative.Thedata were analyzed by reading and identifying which determined through the relationship between the structures and the social problems of the story. The result indicates that intertextuality is established through the social conﬂict relationship. The stories give a portrait on how social situation and discrimination cultural conditions become a reﬂection of society in the era of globalization and information. Keywords: intertextual, essay poetry, social conflict